Effect of six diets during the larval and adult period of Aedes aegypti (Diptera: Culicidae) under laboratory conditions - Sinti-Hesse, Carmen; Tong-Rios, Carlos; Farfán-García, Miguel Angel; Díaz-Soria, Fabiola; Espinoza, José; Zevallos, Karine (Revista Colombiana de Entomología, 2025)
Rearing the laboratory vector Aedes aegypti (Diptera: Culicidae), a disease vector, necessitated diets nutritionally rich in protein and carbohydrates, yet low in fat. The objective of this study was to evaluate and compare the effects of various diets on larval and adult stages, with a specific focus on wing size. Six diets were compared: CIETROP-CC concentrate, fish-based diets (Nutrafin-NF and Aqua One-AO), carnivore-based diets (Ricocan-RC and Supercat-SC), and brewer’s yeast (LV). The development of larval stages was assessed using Kaplan-Meier survival analysis, while wing length was compared using Mood’s median test. The developmental duration from larva to adult was consistent across all six diets, averaging 13 days. Larvae fed LV exhibited a lower survival rate (88 %) compared to the other diets (99%). Female wing size ranged from 2.81 to 2.93 mm, with a mean of 2.88 mm and a standard deviation of 0.12, while male wing size ranged from 2.18 to 2.28 mm, with a mean of 2.23 mm and a standard deviation of 0.17. All diets supported satisfactory larval development, with no significant differences observed in larval survival or developmental duration (P > 0.05). Notably, the CIETROP-CC and commercial diets yielded similar results. These findings indicate that the laboratory-prepared diet exhibited comparable performance to the other five diets in terms of survival and developmental rates. Further analysis will enable the determination of its specific nutritional composition. The results underscore the efficacy of commercial diets in supporting larval.